Taxonomic and functional turnover are decoupled in European peat bogs - Robroek, Bjorn J. M.; Jassey, Vincent E. J.; Payne, Richard J.; Martí, Magalí; Bragazza, Luca; Bleeker, Albert; Buttler, Alexandre; Caporn, Simon J. M.; Dise, Nancy B.; Kattge, Jens; Zając, Katarzyna; Svensson, Bo H.; et al. (Nature communications, 2017)
In peatland ecosystems, plant communities mediate a globally significant carbon store. The effects of global environmental change on plant assemblages are expected to be a factor in determining how ecosystem functions such as carbon uptake will respond. Using vegetation data from 56 Sphagnum -dominated peat bogs across Europe, we show that in these ecosystems plant species aggregate into two major clusters that are each defined by shared response to environmental conditions. Across environmental gradients, we find significant taxonomic turnover in both clusters. However, functional identity and functional redundancy of the community as a whole remain unchanged. This strongly suggests that in peat bogs, species turnover across environmental gradients is restricted to functionally similar species. Our results demonstrate that plant taxonomic and functional turnover are decoupled, which may allow these peat bogs to maintain ecosystem functioning when subject to future environmental change. Peatland plant communities are expected to be affected by environmental change, though how assemblages respond is not fully understood. Here, Robroek et al. show that peatland species occur in two distinct clusters, and functional identity and redundancy was maintained under taxonomic turnover.